Modern biopolymer science : bridging the divide between fundamental treatise and industrial application - Kasapis, Stefan; Norton, Ian T.; Ubbink, Johan B. (Elsevier/Academic Press, 2009)
Industrialists developing new food and pharmaceutical products face the challenge of innovation in an increasingly competitive market that must consider incredient cost, product added-value, expectations of a healthy life-style, improved sensory impact, controlled delivery of active compounds and last, but not lease, product stability. While much work has been done to explore, understand, and address these issues, a gap has emerged between recent advances in fundamental knowledge and its direct application to product situations with a growing need for scientific input. Modern Biopolymer Science matches science to application by first acknowledging the differing viewpoints between those working with low-solids and those working with high-solids, and then sharing the expertise of those two camps under a unified framework of materials science. * Real-world utilisation of fundamental science to achieve breakthroughs in product development * Includes a wide range of related aspects of low and high-solids systems for foods and pharmaceuticals * Covers more than bio-olymer science in foods by including biopolymer interactions with bioactive compounds, issues of importance in drug delivery and medicinal chemistry.